Investigation of cryomilling as a potential tool for the production of amorphous solid dispersions - Hameed, Ghaidaa (2017)
Amorphous solid dispersions over the last decade or so have been widely investigated by the pharmaceutical industry as a formulation method to increase the effective solubility of poorly water soluble drugs and subsequently their bioavailability. Cryomilling is attractive technique to render crystalline materials amorphous without using heat or solvent as are typically used in current processes. The possibility of amorphous formation via cryomilling was studied for three different types of drugs with different glass forming ability (GFA); Felodipine (class III) an easy glass former, paracetamol (class II) a moderate glass former and aspirin (class I) a poor glass former. These drugs were cryomilled alone, cryomilled then mixed with cryomilled hydroxypropyl methylcellulose (HPMC) physically (i.e. cryomilled separately) or co-cryomilled with HPMC together. The subsequent formulations were characterised by DSC, XRPD and FTIR. It was found that when felodipine is cryomilled alone, it can be transformed into the amorphous form, however no amorphous formation was achieved when cryomilling paracetamol or aspirin alone. It is thought that the relatively higher Tg of felodipine compared to paracetamol,and aspirin enables this transformation, however, this transformation was difficult to achieve for paracetamol or aspirin due to their rapid recrystallisation directly after cryomilling due to their low Tg and their resistance to mechanical disorder. Although felodipine was rendered amorphous when milled alone it then recrystallised within a day. It was thought that the conversion of these three drugs into amorphous form or not depends on the glass forming ability of each drug. The amount of polymer required to stabilise the amorphous form of each drug varied according to their glass forming ability with more polymer required for poor glass formers. Felodipine was selected as a model drug for further study with different polymers. This is because felodipine is widely used for the production of amorphous solid dispersion by hot melt extrusion and spray drying. Secondly this drug is practically insoluble but it is an important drug in the emergency treatment of hypertension due its high selectivity and its lack of a negative inotropic effect. Felodipine was co-cryomilled with different polymers and polymer blends that varied in water solubility namely HPMC, HPMCAS, Soluplus R, PMMA, HPMC-HPMCAS, HPMC:PMMA and Soluplus R:HPMCAS at 5, 25, 50 and 75% (w/w) drug loadings. For each mixture the miscibility was predicted using the Gordon-Taylor equation and solubility parameter value. All these mixtures at 50% drug loading were further investigated in dissolution studies for 6 hours under sink condition. All co-cryomilled samples except PMMA showed a high level of drug release (> 90%) after 6 hours dissolution. Only PMMA, which is water insoluble, retarded the release of felodipine from the co-cryomilled mixtures but in ternary mixture felodipine-HPMC/PMMA it showed more than 95% drug release after 6 hours dissolution. As felodipine with Soluplus R showed a good miscibility and stability at 0% humidity and high drug release this co-cryomilled mixture with 50% drug loading was used in the formulation of an orodispersible tablets (ODTs). Six different formulations were manufactured using different superdisintegrants such as F-melt and Glycolate. All the co-cryomilled formulas showed a higher release of felodipine compared to the physical mixtures. Obtaining miscible and stable amorphous solid dispersions without heat or solvent through co-cryomilling is promising as a manufacturing method. Use of heat or solvents can lead to instability in the dispersions and degrade certain drugs. Following this work, amorphous solid dispersions formed via cocryomilling with a high drug loading can be considered for future development for the formulation of fast release dosage form and for drugs liable to thermal or solvent mediated degradation.